THE IMPORTANCE OF FUTUVVAT IN THE UPBRINGING OF A MODERN PERFECT PERSON - Rabbimova Feruza Shamsiddinovna (Journal Park Publishing, 2022)
The article analyzes the importance of the ideas of humanity in the teachings of futuwwat in understanding human perfection and identity, as well as the role of futuwwat in the perfection of man who does not see the struggle between disbelief and faith beyond the material world
Keywords: religion; islam; futuvvat